Teaching peace : toward cultural selflessness - Lasley, Thomas J. ([S.l.] : Praeger, 1994)
Lasley shows how American culture fosters selfishness, aggression, and violence. He believes that selflessness can and should be taught in the home and in the schools as an antidote to the individualism and tribalism that multicultural diversity can lead to. Without a certain cultural and personal respect for the other, the myriad racial, ethnic, and ideological differences could tear American society apart. Lasley uses ethnological examples of non-Western societies that stress nonviolence to elucidate models of peaceful behavior. He provides ways and means of teaching peaceful principles by using the literature of altruism and the images of service and other-directed activities.
Keywords: Moral education; Peace--Study and teaching; Selflessness (Psychology); United States